Family model diabetes self-management education and support in faith-based organizations in the republic of the Marshall Islands study protocol - Pearl A. McElfish; Janine Boyers; Rachel S. Purvis; Betsy O'Connor; Ayoola Carleton; Williamina Bing; Brett Rowland; Craig Molgaard; Ainrik George; Lydia R. Tibon; Dalton Hoose; Sheldon Riklon (Contemporary Clinical Trials Communications, 2021)
Background: Marshallese living in the Republic of the Marshall Islands (RMI) experience significant health disparities, with high rates of type 2 diabetes mellitus. In addition to health disparities, the RMI experienced nuclear testing that exposed inhabitants to nuclear fallout, unethical research practices, and contaminated natural food sources. Objectives: This research uses a community-based participatory research (CBPR) approach to effectively engage community partners and honor their contributions in all stages of the research. A CBPR approach will leverage culturally situated knowledge and practices of the Marshallese community in the RMI to ensure the success of the research. Methods: This manuscript describes the methods used to test the feasibility of delivering a culturally adapted family model of diabetes self-management education and support in faith-based organizations in the RMI. Conclusions: This manuscript describes the protocol for creating working with community partners and implementing a feasibility study in the RMI.